Efficient one-step production of (S)-1-phenyl-1,2-ethanediol from (R)-enantiomer plus NAD+–NADPH in-situ regeneration using engineered Escherichia coli - Zhang Rongzhen; Xu Yan; Xiao Rong; Zhang Botao; Wang Lei (Microbial Cell Factories, 2012)
Abstract Background Candida parapsilosis CCTCC M203011 catalyzes the stereoinversion of (R)-1-phenyl-1,2-ethanediol (PED) through oxidation and reduction. Its NAD+-linked (R)-carbonyl reductase (RCR) catalyzes the oxidization of (R)-PED to 2-hydroxyacetophenone (HAP), and its NADPH-dependent (S)-carbonyl reductase (SCR) catalyzes the reduction of HAP to (S)-PED. The reactions require NAD+ and NADPH as cofactors. However, even if NAD+ and NADPH are added, the biotransformation of (S)-PED from the (R)-enantiomer by an Escherichia coli strain co-expressing RCR and SCR is slow and gives low yields, probably as a result of insufficient or imbalanced redox cofactors. To prepare (S)-PED from the (R)-enantiomer in one-step efficiently, plus redox cofactor regeneration, we introduced pyridine nucleotide transhydrogenases (PNTs) from E. coli to the metabolic pathway of (S)-PED. Results The PNTs were successfully introduced into the E. coli strain RSAB. Most of the PNT activities occurred in the cell membrane of E. coli. The introduction of PNTs increased intracellular NAD+ and NADH concentrations and decreased the NADPH pool without affecting the total nucleotide concentration and cell growth properties. The presence of PNTs increased the NADH/NAD+ ratio slightly and reduced the NADPH/NADP+ ratio about two-fold; the ratio of NADPH/NADP+ to NADH/NAD+ was reduced from 36 to 17. So, the PNTs rebalanced the cofactor pathways: the rate of RCR was increased, while the rate of SCR was decreased. When the ratio of NAD+/NADPH was 3.0 or higher, the RSAB strain produced (S)-PED with the highest optical purity, 97.4%, and a yield of 95.2% at 6 h. The introduction of PNTs stimulated increases of 51.5% and 80.6%, respectively, in optical purity and yield, and simultaneously reduced the reaction time seven-fold. Conclusions In this work, PNTs were introduced into E. coli to rebalance the cofactor pools within the engineered (S)-PED pathways. The efficient one-step production of (S)-PED plus NAD+–NADPH in-situ regeneration was realized. This work provided new insights into cofactor rebalancing pathways, using metabolic engineering methods, for efficient chiral alcohol production.